Bali Tourism Research Trends: A Systematic Review, 1976–2022 - Wiweka, Kadek; Pickel-Chevalier, Sylvine (Jurnal Kajian Bali (Journal of Bali Studies), 2022)
This research aims to systematically review of literature on Bali tourism from 1976 to 2022. This study employed a descriptive quantitative approach and utilizes 128 publications with the keyword “tourism in Bali” sourced from the Scopus database. This study concludes that the development of Bali tourism research has increased significantly. The contribution of Indonesian authors continues to dominate Bali tourism research. International authors play an essential role, especially in introducing the study of Bali tourism in the early thirty years. Furthermore, this review was successful in identifying the most commonly used topics, research approaches, and paradigms by researchers. This research, in particular, divides the evolution of the topics into four phases. The study’s sample of articles is restricted to those from the single database Scopus and solely in English. As a result, future research should be able to analyze articles from other sources, and in a broader range of languages.